Basic Concepts and Approaches of Results Based Management - Bhattarai, Rabindra Nath (Journal of Population and Development, 2020)
The major objective of this paper is to shed light on the conceptual clarity and different approaches of results-based management (RBM). The specific objectives of this paper are to discusses the historical development of RBM, the purpose of RBM and challenges of this management system. This paper is prepared by reviewing primarily on findings from various introductory articles, researches and evaluation reports, reviews conducted by different organisations, institutions, theoreticians, authors and practitioners of development works. By the use of RBM, one can improve efficiency and effectiveness of the organization, fulfill accountability and obligations through performance reporting, assess the management framework with tools for strategic planning, risk management, performance monitoring and evaluation. Moveover, various challenges have been existed in different organizations, which could be solved by using the modern and appropriate results based management system.